Visions of development: faith-based initiatives - Tyndale, Wendy (Ashgate, 2006)
Transformation through self-knowledge and 'awakening'. Swadhyaya: a movement experience in India / R.K. Srivastava(Hindu: India) ; The Sarvodaya Shramadana Movement / by Kamla Chowdhry with Wendy Tyndale (Buddhist: Sri Lanka) ; What kind of development? -- Filling state deficiencies at the grass roots. Association for environmental conservation and social progress: Sarkan Zoumountsi (Chain of Solidarity) / Ibrahim Salissou (Muslim: Cameroon) ; Generosity comes from the strength of the waters: the socio-educational activity of the 'Terreiro' Il(c)® Ax(c)♭ Omin Funk(c)đ / Jussara R(c)®go (Candombl(c)♭: Brazil) ; An experience of development with a Christian and Mayan focus: the case of Awakat(c)Łn / Antonio Otzoy(Christian/Mayan: Guatemala) ; Viable work? -- Tribal people take development into their own hands. Vivekananda Girijana Kalyana Kendra / K.R. Usha (Hindu: India) ; Tokomb(c)♭r(c)♭: a project for human development founded on faith / Etienne Zikra (Christian: Cameroon) ; Faith in ourselves